Effects of Reinforcement by Both Waste Glass and Barley Straw on Water Resistance, Mechanical, and Thermal Properties of Polyethylene Composite - Nadir Ayrilmis; Anton M. Kuzmin; Tahar Masri; Mohamed Yagoub; Lakhdar Sedira; Petr Pantyukhov; Kuwar Mausam; Sivasubramanian Palanisamy; Quanjin Ma; Saleh A Al-Farraj (BioResources)
The water resistance, strength, and thermal properties of the thermoplastic composites were investigated by using different blends of barley stalk flour and waste glass flour as hybrid fillers in HDPE (50 wt%). Virgin E-glass fibers were also used for comparison with the results of the waste glass. The test specimens were prepared by hot-press molding. It was found that the water resistance, tensile strength, and modulus of the HDPE polymer composite prepared with the addition of barley straw flour alone were improved with the use of the waste glass flour and barley straw hybrid. The water absorption (24-h) of the HDPE/barley straw composite was found to be 8.38% while the water absorption decreased to 2.2% in hybrid use with 15 wt% waste glass flour. The addition of the barley straw and waste glass altered the crystalline structure of the HDPE, reducing the melting temperature and melting enthalpy while increasing the crystallinity index. The waste glass provided better thermal stability and a controlled increase in the crystallinity, whereas the glass fiber provided higher crystallinity at the expense of greater disruption to the crystalline structure.